Improved ABR flow control algorithm - LIU Zhi-xin; GUAN Xin-ping; LONG Cheng-nian (Tongxin xuebao)
To improve the performance of traffic management of ATM networks, an improved ABR flow control algorithm was proposed based on discrete model. The effect of the delay elements was considered further with the structure of follow-up control system. The method of choosing parameters, which can guarantee the stability of closed loop time-delay system, was given. The method can avoid the congestion, allocate the available bandwidth fairly and improve the quality of service. The simulation results show that the theory is correct and practical.